A Review on the Role of Honey Bees in Environmental Protection and Maintenance of Ecosystems - Farkhary, Sayed Ibrahim (Journal of Natural Sciences – Kabul University, 2020)
The honey bee is a social insect that plays a crucial role in human life. Honey bee products include honey, pollen, wax, royal jelly, venom, and propolis, which are used daily by humans. In addition to producing these valuable products, the honey bee is the most important pollinator, increasing the quality and quantity of both agricultural and non-agricultural plant fertility through its pollination activities. This review discusses the role of honey bees in enhancing the quality and quantity of plants, conserving biodiversity, and providing food for ecological strains, which are essential for the conservation and maintenance of ecosystems. It also suggests that the absence of honey bees could lead to serious problems and ecosystem damage.